Factors associated with occupational disability classification - Nikolay Angelov; Marcus Eliason (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
Sweden has a long tradition of labour market policies explicitly targeting job seekers with disabilities, ranging from in-work aids to subsidized employments, aiming at strengthening their position at the labour market. To ascertain that these programs are limited to the needy they are constrained to those job seekers that are classified as occu-pationally disabled by the Public Employment Service. In this study we have investi-gated the determinants of being classified as occupationally disabled by the PES. Simi-lar to the studies on disability retirement and self-reported disability we find that men were more likely to be classified as disabled and also that higher age and various meas-ures of socio-economic disadvantages were associated with a higher likelihood. Rather naturally, also all measures indicating poor health were associated with an increased likelihood of being classified as occupationally disabled. A final point is that over the time period under study it became increasingly likely to be classified as occupationally disabled and especially to receive a code related to mental, socio-medical, and learning disabilities.
Keywords: H83; J14; J64; J68; 330; disability; codification; impairment; job seekers; unemployment